Effectiveness of a nutrition and physical activity intervention among adolescent - Bahathig, Abeer Ahmad; Saad, Hazizi Abu; Yusof, Nor Baizura Mohd; Shukri, Nurul Husna Mohd (Intelektual Pustaka Media Utama, 2023)
Unhealthy food intake, physical inactivity, and body image (BI) dissatisfaction could potentially lead to obesity and health problems. This cluster-randomized intervention study aimed to investigate the effectiveness of a nutrition and physical activity (PA) intervention on related knowledge, attitudes, and practices among Saudi adolescent girls (aged 13–14) living in Arar City. One hundred thirty-eight girls were selected and recruited randomly from two schools. The respondents in the intervention group (IG; n=68) received a three-month intervention program that consisted of six 90- minute sessions. The participants in the control group (CG; n=70) received only their traditional education and did not receive the intervention program. The groups’ total pre-test scores for practices were significantly different; therefore, the pre-test scores were used as covariates. The IG demonstrated significant improvements in knowledge, attitudes, and practices (p<0.001 for all), and improvement in the IG was greater than that in the CG at the post- test and three-month follow-up time points (p<0.001 for both). These findings provide evidence of the significant influence of a nutrition, PA, and positive BI intervention on related knowledge, attitudes, and practices among Saudi adolescent girls.